Alkylsilyl Peroxides as Alkylating Agents in the Copper‐Catalyzed Selective Mono‐N‐Alkylation of Primary Amides and Arylamines. Issue 38 (20th June 2017) - Sakamoto, Ryu; Sakurai, Shunya; Maruoka, Keiji
Abstract: The copper‐catalyzed selective mono‐ N ‐alkylation of primary amides or arylamines using alkylsilyl peroxides as alkylating agents is reported. The reaction proceeds under mild reaction conditions and exhibits a broad substrate scope with respect to the alkylsilyl peroxides, as well as to the primary amides and arylamines. Mechanistic studies suggest that the present reaction should proceed through a free‐radical process that includes alkyl radicals generated from the alkylsilyl peroxides. Abstract : Alkylsilyl peroxides : The copper‐catalyzed selective mono‐ N ‐alkylations of primary amides or arylamines using alkylsilyl peroxides as alkylating agents is described. Mechanistic studies suggest that the present reaction should proceed through a free‐radical process that includes alkyl radicals generated from the alkylsilyl peroxides.